Heterogeneidade de fundo de rodolitos expressa em dados de backscatter - Rocha, Gabriella Aleixo (2019)
This study aims at showing the potential of acoustic backscatter mosaic obtained from Multibeam Sonar System (MBSS) to map the cover variation of calcareous algaes nodules along rhodolith beds. Many studies have previously acoustically identified rhodolith beds. However, to verify quantitatively the rhodolith density using MBSS backscatter is a new approach. High-resolution MBSS data were acquired on April 2018, in the Marine Protection Area (MPA) Costas das Algas, located in the Espírito Santo continental shelf. Three areas were selected based on preterit data, totalizing 73km² of data acquisition. The MBSS data were processed on Caris Hips and Sips 9.1.7 software, and three georeferenced backscatter mosaics were created. On June 2018, 80 videos of the seafloor were collected in the areas. These videos were analyzed on the Coral Point Count with Excel Extension Software and used to provide the seafloor type and the percentage of different substrates in each station. The data were segmented into classes based on backscatter intensity variation and ground truth information. As a final result, we identified three classes related to rhodolith in different density: low rhodolith coverage (inferior to 25% of rhodolith), moderate rhodolith coverage (between 25% and 35% of rhodolith), and high rhodolith coverage (greater than 35%). Classes associated with unconsolidated sediment, bioconcretions and red algae genus peyssonelias were also identified. The methodology used in this work is an efficacious tool to map benthic habitats and to detail nodules distribution across a rhodolith bed. It can be used to improve spatial management of marine systems, to monitor and protect vulnerable marine ecosystems.